Politeness in Language in the Comments Column on the TVOne News Youtube Channel “Lesti Billar's Drama Case of Domestic Violence” - Wardatul Jamilah; Yusni Khairul Amri; Bambang Panca Syahputra (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
One form of information and communication media that is very popular at this time is YouTube. This media can be used as a place to share videos with one another, be it videos that provide educational content, tutorials, up-to-date information, or documentary videos of one's personal life. Therefore, the forms of speech contained in YouTube are very diverse. With the various forms of speech contained on YouTube, there are also forms of politeness in speaking. Language politeness according to Geoffrey Leech, namely Geoffrey Leech divides the principles of politeness into six maxims, namely; tact maxim, generosity maxim, appreciation maxim ( approbation maxim), modesty maxim, and sympathy maxim. The author conducted this analysis with the aim of describing language politeness in the comments contained on the Tvonenews YouTube channel entitled Drama Lesti Billar's Domestic Violence Case. The data source in this study is the Tvonenews YouTube channel titled Lesti Billar's Domestic Violence Case Drama which has a video duration of 5 minutes 48 seconds, and was published on October 25 2022. Data analysis was carried out using the politeness maxim. In this analysis it was found that there were five of the six maxims of politeness in Leech's language on the Tvonenews YouTube channel entitled Drama of the Lesti Billar Domestic Violence Case from the 25 data there were 20 data included in the 5 maxims, namely: 4 tact maxims, 2 generosity maxims (generosity maxim), 4 approbation maxims, 3 modesty maxims, and 7 sympathy maxims.